Evaluation of Oral and Dental Health in Patients with Rheumatoid Arthritis: A Prospective Case-Control Study - Salesi, Naghmeh; Rashidi Meibodi, Fatemeh; Shekarchizadeh, Hajar; Mohammadi, Erfan; Salesi, Mansour (Galen Medical Journal, 2024)
Background: Rheumatoid Arthritis (RA) is an autoimmune disease characterized by chronic inflammation. The present study aims to investigate the oral and dental health including periodontal status and decayed, missing, and filled teeth (DMFT) index in RA patients, who were divided into three groups by disease activity score-28 (DAS-28) classification: silent, active, and semi-active. Materials and Methods: This case-control study was conducted during January to December 2022. There were 54 patients in the case group who were divided into three groups based on the DAS index: mild, moderate, and severe. Fifty-four healthy individuals were in the control group. DMFT and DAS-28 indices were used to evaluate the oral health of patients. The evaluation of these indexes was done based on standard questionnaires. The chi-square, Mann-Whitney, and Kruskal-Wallis tests were used to analyze data based on variable type. Analysis was performed at the 95% confidence interval using SPSS software version 24. Results: Patients with severe activity showed more pocket depth and clinical attachment lost (CAL) (p<0.001). No statistical significance was observed in the comparison of DMFT index between the healthy group and patients with mild, moderate, and severe disease activity (p = 0.339); patients had lost more teeth than the control group. (P<0.001). Conclusion: Based on the results, it seems that RA patients with severe activity have a worse condition than the control group. However, according to the result, there was not significant difference in the DMFT index and bleeding on probing among patients with three different severities and healthy individuals.